Simbolisme Mantra Semar Mesem Terhadap Kekuasaan Di Banyuwangi - Wulandari, Intan; Erviantono, Tedi; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
Cultural that is famous in Banyuwangi namely teks Osing, which is a tribal prayer the existence of spiritual magic . This research uses theory Hegemony Gramsci. The method used is qualitative descriptive. The instrument in these study using an in-depth interview on the informant. Determination of informants using techniques purposive sampling and snowball sampling. The results of the research are: first, Semar Mesem as the fine witchcraft of sage used to attract the opposite sex. On progress Semar Mesem can be used as a science magic to gain one's desire to be fulfilled. Second, the symbolic form of use Semar Mesem Belt, heirloom, implant, powder and lipstick. The symbol is used to maintain the position, authority, charm of love and attract the opposite sex. Third, the concept of hegemony Gramsci in use Semar Mesem originated from the doctrine of cultural dominance etnic Osing became heirs and rulers etnik from Banyuwangi which actually people unconsciously follow. Keyword: Qualitative Descriptive, Hegemony, Semar Mesem